SARS-CoV-2 spike antigen-specific B cell and antibody responses in pre-vaccination period COVID-19 convalescent males and females with or without post-covid condition - Marc-André Limoges; Akouavi Julite Irmine Quenum; Mohammad Mobarak Hussain Chowdhury; Fjolla Rexhepi; Mozhdeh Namvarpour; Sara Ali Akbari; Christine Rioux-Perreault; Madhuparna Nandi; Jean-François Lucier; Samuel Lemaire-Paquette; Lakshmanane Premkumar; Yves Durocher; et al. (Frontiers in Immunology, 2023)
BackgroundFollowing SARS-CoV-2 infection a significant proportion of convalescent individuals develop the post-COVID condition (PCC) that is characterized by wide spectrum of symptoms encompassing various organs. Even though the underlying pathophysiology of PCC is not known, detection of viral transcripts and antigens in tissues other than lungs raise the possibility that PCC may be a consequence of aberrant immune response to the viral antigens. To test this hypothesis, we evaluated B cell and antibody responses to the SARS-CoV-2 antigens in PCC patients who experienced mild COVID-19 disease during the pre-vaccination period of COVID-19 pandemic.MethodsThe study subjects included unvaccinated male and female subjects who developed PCC or not (No-PCC) after clearing RT-PCR confirmed mild COVID-19 infection. SARS-CoV-2 D614G and omicron RBD specific B cell subsets in peripheral circulation were assessed by flow cytometry. IgG, IgG3 and IgA antibody titers toward RBD, spike and nucleocapsid antigens in the plasma were evaluated by ELISA.ResultsThe frequency of the B cells specific to D614G-RBD were comparable in convalescent groups with and without PCC in both males and females. Notably, in females with PCC, the anti-D614G RBD specific double negative (IgD-CD27-) B cells showed significant correlation with the number of symptoms at acute of infection. Anti-spike antibody responses were also higher at 3 months post-infection in females who developed PCC, but not in the male PCC group. On the other hand, the male PCC group also showed consistently high anti-RBD IgG responses compared to all other groups.ConclusionsThe antibody responses to the spike protein, but not the anti-RBD B cell responses diverge between convalescent males and females who develop PCC. Our findings also suggest that sex-related factors may also be involved in the development of PCC via modulating antibody responses to the SARS-CoV-2 antigens.